2018
DOI: 10.18542/ragros.v10i2.5131
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura E Dinâmica De Uma Área Manejada Na Floresta Nacional Do Tapajós

Abstract: Objetivou-se, neste estudo, avaliar a estrutura e a dinâmica de uma comunidade arbórea, antes e após a intervenção florestal, na Floresta Nacional do Tapajós. Para isso, instalou-se, aleatoriamente, 10 parcelas permanentes de 50 x 50 m em uma Unidade de Produção Anual (1.000 ha) e realizou-se medições antes e após a intervenção, nos anos de 2012 e 2015, respectivamente. A análise revelou que a extração de madeira provocou alteração no número de indivíduos, área basal e volume, porém não afetou a distribuição d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…According to Knight (1975), the Shannon index for Amazonian forests ranges between 3.83 and 5.85, which is a high value. Studies in both logged and unlogged forests in the Amazon have shown a variation in this index, which may be within the aforementioned range (BEZERRA et al, 2018;SILVA et al, 2011;VIEIRA et al, 2014) or slightly below it (CONDÉ;TONINI, 2013;LIMA et al, 2012). Table 3 shows that the forest targeted in the present study had Shannon indices within the variation commonly observed for the Amazon region when considering the total of species.…”
Section: Diversitymentioning
confidence: 70%
“…According to Knight (1975), the Shannon index for Amazonian forests ranges between 3.83 and 5.85, which is a high value. Studies in both logged and unlogged forests in the Amazon have shown a variation in this index, which may be within the aforementioned range (BEZERRA et al, 2018;SILVA et al, 2011;VIEIRA et al, 2014) or slightly below it (CONDÉ;TONINI, 2013;LIMA et al, 2012). Table 3 shows that the forest targeted in the present study had Shannon indices within the variation commonly observed for the Amazon region when considering the total of species.…”
Section: Diversitymentioning
confidence: 70%
“…Após a colheita de madeira, apesar da maior redução de árvores nas menores classes, a floresta manteve a estrutura na forma exponencial negativa. Esse comportamento também foi observado em outras áreas de manejo florestal na Flona Tapajós (NATIVIDADE et al, 2018;BEZERRA et al, 2018). A manutenção da estrutura da floresta após perturbações antrópicas…”
Section: Avaliação Da Função Densidade De Probabilidade Selecionadaunclassified